2007
DOI: 10.1007/bf02913327
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Immune complexes (CIC) as marker for disease progress in oral cancer

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…Progressively elevated levels were observed in advanced stages of oral cancer patients and patients with PMDs. 30 From these results it can be concluded that CIC represent the host's physiological and immunological defense response in eliciting specific antibodies upon exposure to most antigenic substances.…”
Section: Discussionmentioning
confidence: 90%
“…Progressively elevated levels were observed in advanced stages of oral cancer patients and patients with PMDs. 30 From these results it can be concluded that CIC represent the host's physiological and immunological defense response in eliciting specific antibodies upon exposure to most antigenic substances.…”
Section: Discussionmentioning
confidence: 90%
“…In most cancers, the disease affected tissues generate tumor specific circulating immune cells. As the tumor grows, more tumor antigens were released which may increase the level of circulating Tm cells ( Jane, Nerurkar & Karjodkar, 2007 ; Pages et al, 2005 ; Parcesepe et al, 2016 ). The Tm cells are important for mounting an immune response against the same tumor antigens if they are encountered again.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers [34], [35], [37], [38] reported that the antigenic part of CICs originate from the diseased tissues. Release of antigen from these tissues increases as the disease progresses and that may be responsible for increase in the levels of CICs with increasing grades of PCa which is observed in the present study.…”
Section: Discussionmentioning
confidence: 99%